KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI SPLTV BERDASARKAN TAHAPAN POLYA - Fira Oktarisa; Isnaniah Isnaniah; Nofitatri Purnama (KOLONI, 2022)
The importance of problem-solving skills for student sand the future is the background of this research. According to Polya, there are 4 indicators of problem solving ability, namely understanding the problem, planning the solution, implementing the settlement plan and see ingorre interpreting it. Therefore this study aims to describe students' mathematical problem-solving skills in solving problem son the material system of three-variable line are quations based on Polya stages. This study uses qualitative research with a descriptive approach. The subject susedint his study were 20 students of class X SMA Negeri 3 Bukittinggi. Research data collection techniques using a test description of problem solving abilities as many as 4 questions. From the results of the analysis of the data obtained, it can be concluded that the mathematical problem solving abilities of class X students of SMA Negeri 3 Bukittinggi, totaling 20 people, are divided into high, medium and low categories. Students with high category problem solving abilities totaled 15 people, students with medium category problem solving abilities totaled 4 people and student with low category problem solving abilities totaled 1 person with an average problem solving ability score obtained of 80.27. The students' mathematical problem-solving abilities varied, for the indicator of understanding the problem, the percentage of achievement was obtained by 64.16%, for the indicator for planning completion, the percentage of achievement was obtained by 75%, for indicators of carrying out planning for problem solving, anachievement percentage of 100% is obtained and for indicators of view ingorre interpreting, anachieveent percentage of 63.12% is obtained. Based on these findings, it is hoped that students can study harder by doing more practice on questions, especially SPLTV material and for teachers to be able to differentiate the problem-solving abilities possessed by each student. Keywords: problem solving ability, mathematics, polya